Lacosamide effects on placental carriers of essential compounds in comparison with valproate: Studies in perfused human placentas. Issue 11 (3rd September 2022) - Berman, Erez; Kohn, Elkana; Berkovitch, Matitiahu; Kovo, Michal; Eyal, Sara
Abstract: Objective: Lacosamide is increasingly being prescribed to pregnant women, although its effects on the developing fetus have not been fully clarified yet. Previously, we have shown that several antiseizure medications, particularly valproate, can affect the expression of carriers of essential compounds in placental cells. Here, our aim was to assess the effect of short ex vivo exposure of human placentas to lacosamide on the expression of carriers of essential nutrients required by the human fetus. Methods: Placentas were obtained from cesarean deliveries of women with no known epilepsy. Cotyledons were cannulated and perfused over 180 min in the presence of lacosamide at 2.5 μg/ml (10 μmol·L −1, n  = 7) or 10 μg/ml (40 μmol·L −1, n  = 6), representing low and high therapeutic concentrations, respectively, in the maternal perfusate. Valproate (83 μg/ml, 500 μmol·L −1, n  = 6) and the perfusion solution ( n  = 6) were used as the respective positive and negative controls. A customized gene panel array was used to analyze the expression of carrier genes in the perfused cotyledons. Results: Following a 3‐h perfusion, the mRNA expression of SLC19A1 (encoding the reduced folate carrier 1) was downregulated in placentas treated with 10 μg/ml lacosamide (50%) as compared with the vehicle ( p  < .05). Across all groups, a significant difference was observed in the expression of SLC19A3 (thiamine transporter 2; 52%, 20%, and 9% decrease by 10 μg/ml lacosamide, 83 μg/ml valproate, and 2.5 μg/ml lacosamide, respectively; p  < .05). Significance: Lacosamide at high therapeutic concentrations exerted pharmacological effects on the human placenta. Our findings, if manifested in vivo, suggest that lacosamide could potentially affect folate supply to the fetus and support therapeutic monitoring and careful adjustment of lacosamide plasma concentrations during pregnancy.